PENGARUH STORE ATMOSPHERE, HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN - Astutik, Ayu Dwi; Pujianto, Agung; Maduwinarti, Ayun (Jurnal Dinamika Administrasi Bisnis, 2018)
The competition of retail stores building materials is quite tight. This research test the Influence of Store Atmospher Price and Promotion on Consumer Purchase Decision at Mitra 10 Surabaya. Survey was conducted on 100 consumers of Mitra 10 Wiyung Surabaya. Data analysis using descriptive analysis and analysis path.The result of this research indicates that 1) Store Atmosphere has significant influence to Partial Decision of Purchasing; 2) Price has no significant positive effect on Partial Decision of Purchasing; 3) Promotion positively insignificant to Partial Decision of Purchasing; 4) Simultaneously variable Store atmospher, Price, and Promotion have a significant effect on purchasing decision; 5) Store Atmosphere dominant influence on purchasing decisions. Keywords: Store Atmospher, Price, Promotion, Purchase Decision